Estudo experimental da tecnologia dual-fuel em motor de combustão interna utilizando biogás, GNV e etanol - Roberto Berlini Rodrigues da Costa (2017)
Energy is the key to longevity of modern civilization and its demand continues to increase. With the end of oil availability and world energy crisis perspectives, technological solutions are needed from the scientific community to promote the reduction of fossil fuel consumption, the maximization of fuel conversion efficiency and the reduction of emission levels in internal combustion engines. Aiming to reach these needs, the use of biogas, a biofuel derived from the reuse of waste, in dual-fuelinjection systems is a technology with potential. Economy and ecology are engaged in a clinch and the search for alternatives has begun. Therefore, this work aimed to characterize and analyze a dual-fuel injection system adapted to a single-cylinder spark-ignition engine, using blends of biogas-ethanol and natural gas-ethanol as fuels. The application of this work is focused on load and operation regimes of motorgenerators. The methodology consisted in the engine selection and setup, design and manufacture of new components, preparation of fuels and injection systems, instrumentation used, measurement uncertainty method, test bench assembly, test and calibration methodologies and analysis of the parameters of interest. Experiments were divided into three stages: tests with only one fuel, tests with dualfuel technology and tests with internal exhaust gas recirculation (iEGR). The results obtained with the dual-fuel strategies show an increase in fuel conversion efficiency up to 10% for blends of biogas-ethanol and 3% for blends of natural gas-ethanol, in addition to emission levels reduction of NOx, HC and CO. The strategy of using iEGR increased both thermal and combustion efficiency and reduced NOx emissions by approximately 60%. In this way, the dual-fuel injection system for spark-ignition engines developed has wide application and marketability integration, as analternative technology able to help meeting the energy demands in a sustainable manner